Some comments on the structure of the poem (Eurasian Journal of Humanities and Social Sciences, 2022)
Poems are a collection of literary work written by poets in stanzas and lines that make use of rhythm in order to emphasize or express emotions and ideas. The structure of the poem is related to the specific language, thinking, consciousness, and tradition of each nation. If we talk about the structure of the poem, we understand it as a method that organizes the rhythm and tone of poetic speech; Poetic speech differs from prose speech according to the rules of poem structure and strict adherence to these rules. The structure of the poem is actually a complex system of its own. Because many ideological and artistic elements are involved in the creation of a poem. In particular, a poem emerges from the combination of elements such as theme, idea, refrain, rhythm, tone, intonation, pause, accent, poetic symbols, phonetic methods, artistic arts, plot, symbol, composition, conflict that are united into a clear and a single system. This article provides an overview on the structure of a poem in Uzbek and English languages